2008
DOI: 10.1590/2175-7860200859204
|View full text |Cite
|
Sign up to set email alerts
|

Diatomáceas em sedimentos superficiais na planície de maré da Praia de Itupanema, estado do Pará, Amazônia

Abstract: RESUMO O objetivo deste artigo é avaliar a composição, abundância e riqueza das diatomáceas presentes na zona intermaré da Praia de Itupanema e relacionar esses atributos à hidrodinâmica atual, evidenciada pela textura do sedimento. Foram coletadas 10 amostras em duas transecções perpendiculares, em intervalos de 5 m nas coordenadas 01º31'03"S e 48º43'28"W em março de 2006, sendo analisadas segundo as técnicas convencionais no estudo de diatomáceas. Os resultados mostraram a ocorrência de 58 espécies, 82,75% b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 19 publications
0
14
0
4
Order By: Relevance
“…However, the planktonic diatoms were more abundant in clay sediments, in the calmer sedimentation conditions. Otherwise, the benthic/epiphytic species were more numerically important, when attached to sand and claysand sediments, indicating more energy from waves and tides, under erosive conditions (Ribeiro et al, 2008). Ribeiro et al (2008) reported that the autochthonous community, represented by benthic/epiphytic species, occupied several substrates, from sandy to clay sediments, in addition to herbaceous vegetation at the sampling area.…”
Section: Modern Distribution Of Diatoms At Itupanema Beachmentioning
confidence: 96%
See 4 more Smart Citations
“…However, the planktonic diatoms were more abundant in clay sediments, in the calmer sedimentation conditions. Otherwise, the benthic/epiphytic species were more numerically important, when attached to sand and claysand sediments, indicating more energy from waves and tides, under erosive conditions (Ribeiro et al, 2008). Ribeiro et al (2008) reported that the autochthonous community, represented by benthic/epiphytic species, occupied several substrates, from sandy to clay sediments, in addition to herbaceous vegetation at the sampling area.…”
Section: Modern Distribution Of Diatoms At Itupanema Beachmentioning
confidence: 96%
“…The planktonic diatoms are supplanted by benthic forms in number of species and relative abundance on the surface sediments of the Itupanema Beach, indicating that hydrological conditions were unfavorable for sedimentation of the planktonic diatoms from the water column (Ribeiro et al, 2008). However, the planktonic diatoms were more abundant in clay sediments, in the calmer sedimentation conditions.…”
Section: Modern Distribution Of Diatoms At Itupanema Beachmentioning
confidence: 97%
See 3 more Smart Citations

Primary Producers

Odebrecht,
de Oliveira da Rocha Franco,
Horta
et al. 2023
Brazilian Marine Biodiversity